Microplasma-enhanced synthesis of colloidal graphene quantum dots at ambient conditions. (November 2019) - Yang, Jhih-Siang; Pai, David Z.; Chiang, Wei-Hung
Abstract: Here we report a bottom-up method to synthesize colloidal graphene quantum dots (GQDs) using microplasmas at ambient conditions. As-produced colloidal GQDs show 4.9 nm averaged diameter and exhibit room-temperature photoluminescence that peaks at 448 nm with a quantum efficiency of 1.5%. Solvated electrons (eaq − ) generated by the microplasma interacting with the precursor solution were found to be critical for the GQD formation. Our study provides a simple method to synthesize colloidal GQDs and the insight to understand the fundamental factors involved in nano-sized graphene synthesis by microplasma-assisted liquid phase chemistry.